Prevalensi dan Intensitas Ektoparasit pada Insang Ikan Nila Merah (Oreochromis sp.) di Keramba Apung Sungai Kapuas Desa Kapur Kabupaten Kubu Raya - Diah Wulandari, Irwandi, Ari Hepi Yanti (Universitas Tanjungpura, 2017)
Red tilapia (Oreochromis sp.) are cultured in floating cages of the Kapuas River in Kapur Village can be infected with ectoparasites, especially on the gills. This study aims to determine the types, prevalence and intensity of ectoparasites on the gills of red tilapia in floating cages of the Kapuas River in Kapur Village of Kubu Raya Regency. The samples were taken in April 2016 by random sampling method. The fish as many as 100 individuals were taken randomly from the floating cages in five locations. Ectoparasites were found consisting of two types which are members of the Class Monogenea, namely Dactylogyrus sp. and Gyrodactylus sp. The ectoparasite Dactylogyrus sp. mostly infected the red tilapia gills with the value of the average prevalence of 90% (infection category of almost always) and the value of the average intensity of 3.97 ind/individual. The Gyrodactylus sp. found on the gills had a value of the average prevalence of 49% (infection category of commonly) and the average intensity value of 1.76 ind/individual.